Willingness of Brazilian dentists to treat an HIV-infected patient - Sposto, M. R.; Goncalves, F.; Ferracioli, A.; Porter, S. R.; Afonso, W.; El-Maaytah, M.; Di Alberti, L.; Scully, C. (Elsevier, 1994)
A study of the willingness of 363 general dental practices in Brazil to accept a patient infected with human immunodeficiency virus for treatment of dental pain and the provision of routine dental care showed only 44% of dental practices to be willing to provide dental care. Willingness was influenced neither by financial factors nor the local prevalence of human immunodeficiency virus disease. © 1994.
Keywords: survey; adult; attitude; Brazil; Clinical Approach/Source; dental care; dentist; Empirical Approach; evaluation; general practice; Health Care and Public Health; human; Human immunodeficiency virus infection; male; patient referral; Professional Patient Relationship; psychological aspect; tooth pain; Evaluation; Survey; Adult; Attitude of Health Personnel; Dental Care for Chronically Ill; Dentists; General Practice, Dental; HIV Seropositivity; Human; Male; Referral and Consultation; Refusal to Treat; Toothache